(untitled) (Caderno Espaço Feminino, 2019)
Utilizando a concetualização de disciplinamento social, o texto tem como objetivo perceber como se sensibilizam as mulheres para a prática do exercício físico, nas páginas da revista Fémina, ao longo da década de 1930. Procurando captá-las através de um discurso que apelou à vaidade, em muitos artigos o que esteve em causa foi a obtenção de um corpo saudável com vista a gerar crianças robustas, de acordo com os ideais políticos da época. PALAVRAS-CHAVE: Ginástica. Fémina. Raça. Portugal. anos de 1930. ABSTRACT Using the conception of social discipline, the text aims to understand how women are sensitized to the practice of physical exercise, in the pages of Fémina magazine, throughout the decade of 1930. Looking to capture them through a speech that appealed to vanity, in many articles, what was at stake was the attainment of a healthy body in order to generate robust children, according to the political ideals of the time. KEYWORDS: Gymnastics. Fémina. Race. Portugal. 1930s.